Product identification problems using Industry 4.0 technologies - Tóth, Lajos; Akylbek, Umetaliev; Cservenák, Ákos; Bányai, Tamás; Illés, Béla; Tamás, Peter (Journal of Production Engineering, 2020)
Industry 4.0 technologies have the potential to enhance not only the performance of manufacturing and assembly processes but also to increase the efficiency of associated logistics operations. In this article, we present a system that leverages Industry 4.0 technologies to identify product mixing issues. The identification of loading unit construction equipment and products is facilitated through the use of RFID tags. We employ an Excel format database file to store the binding matrix of the products. Additionally, we have developed software that controls our industrial IF30 RFID reader. This software also conducts a product mix detection test.